Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1515/bc.2008.160
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 and 2 regulate the capacity of mesangial cells to resist apoptotic stimuli in an opposing manner

Abstract: Sphingosine kinases (SKs) are key enzymes regulating the production of sphingosine-1-phosphate (S1P), which determines important cell responses including cell growth and death. Here we show that renal mesangial cells isolated from wild-type, SK-1 -/-, and SK-2 -/-mice show a differential response to apoptotic stimuli. Wildtype mesangial cells responded to staurosporine with increased DNA fragmentation and caspase-3 processing, which was enhanced in SK-1 -/-cells. In contrast, SK-2 -/-cells were highly resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…In this context, Hofmann et al [13] investigated the role of the two SK isoforms, SK-1 and SK-2, in staurosporine induced apoptosis. They showed that renal MCs isolated from SK-2 knockout mice were resistant to staurosporine-induced apoptosis whereas the absence of SK-1 led to a more pronounced apoptotic response to staurosporine.…”
Section: S1p In Renal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Hofmann et al [13] investigated the role of the two SK isoforms, SK-1 and SK-2, in staurosporine induced apoptosis. They showed that renal MCs isolated from SK-2 knockout mice were resistant to staurosporine-induced apoptosis whereas the absence of SK-1 led to a more pronounced apoptotic response to staurosporine.…”
Section: S1p In Renal Cellsmentioning
confidence: 99%
“…Because of its highly bioactive properties S1P is an attractive target for the treatment of several diseases. Since the expression of SKs as well as S1PRs was demonstrated in kidney lysates as well as in isolated renal cells [8,9,10,11,12,13], questions about the physiological and pathophysiological functions of S1P in this organ have been raised. Here, we summarize the current state of knowledge about S1P-mediated functions in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…An unusual pathway in mammalian cells for the salvage of sphingosine back into ceramide has been uncovered that requires its phosphorylation by SphK2 (but not SphK1) and then dephosphorylation by SPP1 (but not SPP2) before it can be reacylated to ceramide by CerS (11). Similarly, renal mesangial cells isolated from SphK2-, but not SphK1-knockout mice, had increased levels of sphingosine (12). This seemingly futile cycle has previously been demonstrated to occur in yeast (13), suggesting that this is an evolutionarily conserved pathway.…”
Section: Opposing Roles Of Sphk1 and Sphk2 In Sphingolipid Metabolism?mentioning
confidence: 99%
“…22,[35][36][37] Mice overexpressing the human Sphk2 gene were generated by GenOway (Lyon Cedex, France). Briefly, human Sphk2 transgene controlled by the ubiquitous CAG promoter was introduced into the Hprt locus by homologous recombination.…”
Section: Animal Proceduresmentioning
confidence: 99%